Freedom in handcuffs: religious freedom in the constitution of China - Li, Songfeng (Journal of law and religion, 2020)
Article 36 of the Chinese Constitution tells only part of the story about religious freedom in China. The Chinese constitution establishes five restrictions on the religious freedom described in Article 36. First, the Chinese Constitution establishes state atheism as an official ideology. All Chinese citizens, whether religious believers or not, are required to be educated in Marxist ideology and under the leadership of the Chinese Communist Party. Second, religious freedom, along with other rights in the Chinese Constitution, are merely legal rights, rather than fundamental rights. The National People's Congress can therefore pass legislation limiting individuals’ religious freedom. Third, the Chinese Constitution enumerates basic obligations of citizens that limit religious freedom. Fourth, Article 36 protects only the inner freedom of religious belief, not freedom for religious practice. Finally, the second half of Article 36 places limitations on religious practices. Religious freedom in the Chinese Constitution is thus a highly limited freedom. To improve religious freedom protections in China it is necessary to amend the Constitution rather than simply promote full implementation in its current form.